Cognitive Profiles of Reading-Disabled Children: Comparison of Language Skills in Phonology, Morphology, and Syntax - Shankweiler, D.; Crain, S.; Katz, L.; Fowler, A.E.; Liberman, A.M.; Brady, S.A.; Thornton, R.; Lundquist, E.; Dreyer, L.; Fletcher, J.M.; Stuebing, K.K.; Shaywitz, S.E.; et al. (Psychological Science, 1995)
A comprehensive cognitive appraisal of elementary school children with learning disabilities showed that within the language sphere, deficits associated with reading disability are selective Phonological deficits consistently accompany reading problems whether they occur in relatively pure form or in the presence of coexisting attention deficit or arithmetic disability Although reading-disabled children were also deficient in production of morphologically related forms, this difficulty stemmed in large part from the same weakness in the phonological component that underlies reading disability In contrast, tests of syntactic knowledge did not distinguish reading-disabled children from those with other cognitive disabilities, nor from normal children after covarying for intelligence